Circularly‐Polarized Electrochemiluminescence from a Chiral Bispyrene Organic Macrocycle. (16th April 2019) - Zinna, Francesco; Voci, Silvia; Arrico, Lorenzo; Brun, Elodie; Homberg, Alexandre; Bouffier, Laurent; Funaioli, Tiziana; Lacour, Jérôme; Sojic, Neso; Di Bari, Lorenzo
Abstract: The first observation of circular polarization of electrochemiluminescence (ECL) from a purely organic derivative is reported. A bispyrene scaffold mounted on a constrained polyether macrocycle displaying intense excimer fluorescence and highly circularly‐polarized (CP) photoluminescence has been selected for this purpose. The compound displays an ECL dissymmetry factor of about |8×10 −3 |, which is in good agreement with the corresponding photoluminescence value. This observation is the first step towards the molecular engineering of tailored dyes that can act as both ECL and CP‐ECL reporters for (bio)analysis by bringing a new level of information when dealing with chiral environments. Additionally, it provides an extra dimension to the ECL phenomenon and opens the way to chiral detection and discrimination.